2015
DOI: 10.1080/10426914.2015.1019127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Cryogenic Cooling in the Drilling of Titanium Alloy

Abstract: In this study, a drilling experiment was conducted on titanium ASTM B265 Grade 2 material using PVD coated carbide inserts. Two types of coolants (Wet and LN 2 ) were used. The variables in the experiment were feed rate (f) and cutting speed (V c ). The depth of the drilling was constant. Cutting temperature (T), thrust force (F t ), surface roughness (R a ), and the hole quality (circularity, cylindricity, and perpendicularity) were analyzed. The tool wear and chip morphology were studied. The result of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 14 publications
(12 reference statements)
2
16
0
Order By: Relevance
“…The maximum hole perpendicularity error value occurred at a feed rate of f = 900 mm/ min and was minimum at a feed rate of f = 300 mm/min. Similar trends were observed by previous researchers when drilling aluminum and titanium alloys [42,43]. Generally, it was observed that hole perpendicularity error increased with the increase of the feed rate for all depths of cuts which is mainly due to the increase in the feed force as it can be seen from Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The maximum hole perpendicularity error value occurred at a feed rate of f = 900 mm/ min and was minimum at a feed rate of f = 300 mm/min. Similar trends were observed by previous researchers when drilling aluminum and titanium alloys [42,43]. Generally, it was observed that hole perpendicularity error increased with the increase of the feed rate for all depths of cuts which is mainly due to the increase in the feed force as it can be seen from Fig.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies investigated the effect of cutting parameters, tool coating, tool geometry, and coolants on hole perpendicularity error for a variety of metallic materials such as steel, aluminum, and titanium alloys [37][38][39][40][41][42][43][44][45][46] and composite materials [36,47]. The studies found that three most significant variables on hole perpendicularity error were cutting speed, feed rate, and depth of cut [40][41][42][48][49][50]. Other studies reported that the application of machining coolants did not have an influence on the hole dimensional and positional accuracy such as its perpendicularity error and cylindricity expect for certain cases, which was mainly attributed to the size and type of cutting tool used [40].…”
Section: Introductionmentioning
confidence: 99%
“…High temperature in the machining process of such steel limits the usage of carbide cutting tools if effective cooling and/or lubrication are not implemented [1]. The conventional cooling approach is accepted as an effective way for most applications, but from an environmental standpoint, it is not always the way preferred by the machining community [3][4][5]. Therefore, dry machining [6] is used in the machining process of hardened steel [7].…”
Section: Introductionmentioning
confidence: 99%
“…Large consumption of cutting fluids used in manufacturing industries affects human workers health, pollution problems, recycling and disposal costs [3]. Cryogenic cooling is a new coolant approach used as a replacement of cutting fluids [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%